(3GdSjQI GdeSJbjeIs ((3GdCejQ YjSi Hf GdJfhNi s)
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe HSe dGdg GdQMef GdQMje UaGJ YHOg GdEeGe QShe GdfWbGA GdMThjI hePGgH GdXGgQ GdfGehSjI s
(3BNQgG (B:s
(3hEPG YHOJehg adCfaSce egOJe hEf caQJe HdGghJg aYdjce GdNRi hGdYPGH hGdMeO hGdTcQ dehdGfG hMOg ai GdSQGA hGdVQGA hGdTOI hGdQNGA JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds